Organizational Mindfulness Assessment and Its Impact on Rational Decision Making - Yuli L. León; Enrique Mu (Mathematics, 2021)
Ever since its appearance in the organizational research literature, the importance of organizational mindfulness has consistently increased. For this reason, this study has the following two research objectives: first, to explore the positive effect of organizational mindfulness (OM) on the rationality of the decision-making process and second, to propose a framework to assess the extent of its presence in organizations. For the first objective, exploratory partial least square structure modeling (PLS-SEM) was conducted, while for the second goal, an evaluation framework based on the Analytic Hierarchy Process (AHP) was developed. Surveying 117 decision-making leaders in the field, organizational mindfulness and its constitutive processes that include resistance to simplify interpretations, preoccupation with failure, sensitivity of operations and commitment to resiliency with deference to expertise, were empirically studied. A significant positive effect of these dimensions and OM as a whole on the rationality of the decision-making process was statistically shown. For this reason, it is important to assess the extent of the presence of organizational mindfulness in organizations. The use of this AHP-based OM evaluation framework is demonstrated for the case of the complex health sector in Colombia.